Improvements to the digital curling system - Mori, K.; Higuchi, T.; Ito, T. (Workshop on Curling Informatics 2018, 2018)
"Digital Curling" is a system for analyzing curling strategies. Curling AIs are developed ova- time and problems of the system are illuminated. In this study, wj; reconstruct and improve the system to make it more flexible. We will hold a toumament with a different rule called "Mix Doubles" with the improved system.